Preparation method and application of a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst
Patent Information
- Application Number
- CN202611378165.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-16
AI Technical Summary
然而,降解反应需强氧化性空穴参与,H2O2生成则依赖定向电子转移,二者对载流子的有效空间分离及2e-氧还原选择性提出了双重挑战
1、本发明采用绿色机械研磨固相法,在保持CoZn-ZIF等网格骨架不变的前提下,通过调控Co/Zn摩尔比及合成条件,实现了原子级配位环境与纳米级晶粒形貌的协同精确控制。所得材料凭借稳定的骨架结构和可调变的电子态,显著提升了两电子氧还原反应(2e-ORR)的选择性与催化效率,展现出优异的助催化性能。
Smart Images

Figure CN122912923A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalysis technology, and in particular to a method for preparing a bimetallic MOF / zinc indium sulfide (ZnIn2S4) heterojunction photocatalyst and its application. Background Technology
[0002] Hydrogen peroxide (H2O2) is an important green oxidant and a potential energy carrier, with broad application prospects in promoting sustainable chemistry. Currently, the industrial production of hydrogen peroxide mainly uses the anthraquinone process; however, this process involves toxic organic solvents and produces high yields of byproducts such as waste liquid and residue.
[0003] While photocatalytic synthesis of H2O2 from water and oxygen is a green alternative, traditional systems rely heavily on sacrificial agents (such as isopropanol) to suppress carrier recombination. This method is not only reagent-intensive but also limits yield. Specifically, on the one hand, photogenerated electron-hole pairs are prone to bulk recombination; on the other hand, the 2e- electrons in the oxygen reduction reaction... - With 4e - There is competition for pathways, and side reactions on non-target pathways significantly reduce the selectivity and formation rate of H2O2.
[0004] Therefore, this invention proposes a photocatalytic design concept for simultaneous pollutant degradation and in-situ H2O2 synthesis, aiming to implement a circular economy-oriented wastewater treatment strategy. Its core idea is to utilize pollutants to consume photogenerated holes, while simultaneously using photogenerated electrons to drive selective 2e- ... - Oxygen is reduced to produce H₂O₂. However, the degradation reaction requires the participation of strongly oxidizing holes, while H₂O₂ formation depends on directional electron transfer. Both factors affect the effective spatial separation of charge carriers and the 2e⁻ content. - Oxygen reduction selectivity presents a dual challenge. To address this, this invention loads bimetallic ZnCo-ZIF nanoparticles (with a highly tunable zeolite imidazole framework) onto the surface of flower-like ZnIn2S4 (ZIS), constructing a ZnCo-ZIF / ZnIn2S4 (ZnCo-ZIF / ZIS) heterojunction photocatalyst. Band matching creates a strong built-in electric field at the interface, driving electrons and holes to their respective active sites, effectively extending carrier lifetime. This enables simultaneous, non-interfering bifunctional reactions, balancing photoelectric conversion and water purification. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a simple and efficient method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst.
[0006] Another technical problem to be solved by the present invention is to provide the application of this bimetallic MOF / zinc indium sulfide heterojunction photocatalyst.
[0007] To address the above problems, the present invention provides a method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst, comprising the following steps: Preparation of bimetallic cobalt / zinc imidazole organic framework CoZn-ZIF nanoparticles by S1 mechanical milling solid-state method: Zinc nitrate (Zn(NO3)2·6H2O) and cobalt nitrate (Co(NO3)2·6H2O) were mixed and ground, and then 2-methylimidazole was added. After mixing, the mixture was transferred to a stainless steel grinding jar equipped with steel balls for mechanical grinding. The resulting product was washed, centrifuged, and vacuum dried to obtain a purple solid powder, which was denoted as CoZn-ZIF nanoparticles. Preparation of flower-like ZnIn2S4 materials by S2 hydrothermal method: Zinc nitrate (Zn(NO3)2·6H2O) and indium nitrate (In(NO3)3·4H2O) were dispersed in an excess solvent, and then thioacetamide (C2H5NS) was added. After magnetic stirring until completely dissolved, the resulting mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal reaction. After the reaction was completed, the solution was cooled to room temperature, centrifuged, washed, and vacuum dried to obtain a flower-shaped brown ZnIn2S4 product, denoted as ZIS. Preparation of CoZn-ZIF / ZIS heterojunction photocatalysts using S3: CoZn-ZIF nanoparticles and ZIS were dispersed in excess anhydrous methanol, and after magnetic stirring, centrifugation and vacuum drying were performed to obtain the CoZn-ZIF / ZIS heterojunction photocatalyst.
[0008] In step S1, the molar ratio of zinc, cobalt, and 2-methylimidazole is (0.1~0.4 mmol):(0.2~0.8 mmol):(0.004~0.008 mmol).
[0009] The mechanical grinding conditions in step S1 refer to a frequency of 20~60Hz and a time of 20~80min.
[0010] In step S2, the mass ratio of zinc nitrate, indium nitrate, and thioacetamide is 0.1~0.8g: 0.3~1.2g: 0.1~0.8g; the solvent is one of ethylene glycol, N,N-dimethylformamide, and anhydrous methanol.
[0011] The hydrothermal reaction conditions in step S2 refer to a temperature of 120~180℃ and a time of 6~14h.
[0012] In step S3, the amount of CoZn-ZIF nanoparticles used is 2.5% to 10% of the ZIS mass.
[0013] The conditions for magnetic stirring in step S3 are a speed of 800~1300 rpm and a time of 2~6h.
[0014] A CoZn-ZIF / ZIS heterojunction photocatalyst was prepared by the method described above.
[0015] The application of the CoZn-ZIF / ZIS heterojunction photocatalyst described above is characterized in that the catalyst is used in the photocatalytic production of H2O2 from pure water or wastewater.
[0016] The photocatalytic H2O2 production process is as follows: Pure water is placed in a photocatalytic reactor without a sacrificial agent. Oxygen is introduced, and the photocatalyst CoZn-ZIF / ZIS is added in a saturated oxygen atmosphere. After dark adsorption for 30 minutes, a visible light source is turned on to carry out the photocatalytic reaction at room temperature, i.e., H2O2 is generated in situ; or Wastewater was placed in a photocatalytic reactor, with bisphenol A, an organic pollutant in the wastewater, as a sacrificial agent. Oxygen was introduced, and the photocatalyst CoZn-ZIF / ZIS was added in a saturated oxygen atmosphere. After dark adsorption for 30 min, a visible light source was turned on to carry out the photocatalytic reaction at room temperature, so as to simultaneously generate H2O2 and degrade the organic pollutant bisphenol A.
[0017] The concentration of bisphenol A in the wastewater is 5-30 mg / L; the pH of the wastewater is 4-9; the dosage of the photocatalyst CoZn-ZIF / ZIS is 0.20-0.50 mg / mL; the wavelength of the visible light source is >420 nm, and the light intensity is ≥1.5 W / cm². 2 .
[0018] Compared with the prior art, the present invention has the following advantages: 1. This invention employs a green mechanical grinding solid-state method. While maintaining the CoZn-ZIF network framework, it achieves precise and coordinated control of the atomic-level coordination environment and nanoscale grain morphology by adjusting the Co / Zn molar ratio and synthesis conditions. The resulting material, with its stable framework structure and tunable electronic states, significantly enhances the two-electron oxygen reduction reaction (2e⁻¹). - The selectivity and catalytic efficiency of ORR demonstrate excellent co-catalytic performance.
[0019] 2. This invention constructs a CoZn-ZIF / ZnIn2S4 heterojunction with an optical absorption edge down to 780 nm, and a built-in electric field promotes directional electron-hole separation. The hydrophobic ZIF enriches O2, which is beneficial for 2e- electron separation. - The reduction process, with hydrophilic ZIS providing a fast proton pathway, synergistically accelerates electron consumption, inhibits recombination, and stabilizes the intermediate state OOH. * Inhibit 4e -Side reactions enhance the selectivity and yield of H2O2. Spatially isolated reduction and oxidation reactions enable parallel and efficient H2O2 synthesis and pollutant degradation, endowing the system with bifunctional photocatalytic properties.
[0020] 3. The CoZn-ZIF / ZnIn2S4 photocatalyst described in this invention can achieve an H2O2 yield of 2277 µmol·g in a pure water system (visible light, air atmosphere, no sacrificial agent). -1 ·h -1 ; In the presence of BPA (20 mg·L -1 In the simulated wastewater system, the H2O2 yield increased instead of decreasing, reaching as high as 2236.5 µmol·g. -1 ·h -1 Meanwhile, the BPA degradation efficiency reached 60.5%. This "positive synergistic effect" phenomenon breaks through traditional understanding and fully demonstrates that the system can still maintain excellent redox dual-function activity under actual complex water quality conditions.
[0021] 4. This invention eliminates the dependence of traditional H2O2 synthesis on high-purity water, organic sacrificial agents, and external bias voltage. It uses only air, visible light, and phenol-containing wastewater as inputs to simultaneously produce high-value-added chemicals and reduce environmental pollutants in the same reactor, realizing a green closed loop of "treatment + production capacity". It has both atom economy and energy self-sufficiency, providing a new path for the practical application of photocatalysis technology in water treatment and energy recovery. Attached Figure Description
[0022] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0023] Figure 1 This is a schematic diagram of the process for synthesizing the bimetallic imidazole organic framework CoZn-ZIF by mechanical grinding solid-state method in this invention.
[0024] Figure 2 The images show X-ray diffraction (XRD) patterns of ZIF-8, ZIF-67, bimetallic CoZn-ZIF with different Co / Zn molar ratios, and the corresponding CoZn-ZIF / ZIS heterojunction composite samples obtained in Examples 1-3 and Comparative Examples 1-4 of this invention. Specifically: (a) shows ZIF-8 prepared by liquid-phase and solid-phase methods; (b) shows ZIF-67 prepared by liquid-phase and solid-phase methods; (c) shows bimetallic imidazole framework CoZn-ZIF with different Co / Zn molar ratios prepared by solid-phase method; and (d) shows the CoZn-ZIF / ZnIn2S4 (ZIS) heterojunction composite sample.
[0025] Figure 3The Fourier transform infrared (FT-IR) spectra of ZIF-67, bimetallic CoZn-ZIF with different Co / Zn molar ratios, and corresponding CoZn-ZIF / ZIS heterojunction composite samples obtained in Examples 2-3 and Comparative Examples 3-5 of this invention are shown. (a) shows ZIF-67 and bimetallic CoZn-ZIF with different Co / Zn molar ratios prepared by liquid-phase and solid-phase methods; (b) shows ZIS and CoZn-ZIF / ZIS heterojunction composite samples.
[0026] Figure 4 XPS spectra of ZIF-67, bimetallic CoZn-ZIF, and CoZn-ZIF / ZIS samples obtained in Example 3 and Comparative Example 3 of this invention. Wherein: (a) is the full spectrum analysis of CoZn-ZIF / ZIS; (b) is Co 2p; (c) is Zn 2p; (d) is S 2p; (e) is In 3d.
[0027] Figure 5 SEM images of ZIF-67, bimetallic CoZn-ZIF, ZIS, and CoZn-ZIF / ZIS samples obtained in Example 3 and Comparative Example 4 of this invention are shown. (a) shows ZIF-67 prepared by liquid-phase method; (b) shows ZIF-67 prepared by mechanical grinding solid-phase method; (c) shows CoZn-ZIF prepared by solid-phase method; (d) shows ZnIn2S4 (ZIS); and (e) shows 5% Co... 0.5 Zn 0.2 -ZIF / ZIS; (f) is 5%Co 0.5 Zn 0.2 -ZIF / ZIS sample EDS spectrum.
[0028] Figure 6 The images show the ultraviolet diffuse reflectance of samples ZIF-8, ZIF-67, bimetallic CoZn-ZIF, and CoZn-ZIF / ZIS obtained in Examples 1-3 and Comparative Examples 2 and 4 of this invention.
[0029] Figure 7 The fluorescence spectra of the ZIS, ZIF-67 / ZIS, and CoZn-ZIF / ZIS samples obtained in Examples 1-3 and Comparative Example 5 of this invention are shown.
[0030] Figure 8 The transient photocurrent and electrochemical impedance spectroscopy (EIS) spectra of the ZIS, Co-ZIF / ZIS, and CoZn-ZIF / ZIS samples obtained in Examples 2-3 and Comparative Example 5 of this invention are shown. (a) is the transient photocurrent spectrum; (b) is the electrochemical impedance spectroscopy.
[0031] Figure 9This invention, in Example 4, demonstrates the application of photocatalytic H2O2 production from different samples in a pure water system under visible light irradiation. Wherein: (a) is the absorption spectrum of pure phase ZnIn2S4 (ZIS); (b) is the absorption spectrum of 5% Co... 0.5 Zn 0.2 (c) The absorption spectrum of ZIF / ZIS heterojunction; (d) The comparison of the photocatalytic H2O2 production rates of different samples; (e) The average H2O2 yield of pure phase ZIS, monometallic ZIF-67 / ZIS heterojunction and bimetallic CoZn-ZIF / ZIS heterojunction after 120 min of illumination.
[0032] Figure 10 The standard curve for the determination of H2O2 by iodometric titration is shown. Among them: (a) is the absorption curve; (b) is the standard working curve.
[0033] Figure 11 This is a spectral diagram of the generation of H2O2 and the synergistic degradation of BPA pollutants in a bisphenol A wastewater system according to Example 5 of the present invention. Wherein: (a) is the absorption spectrum of H2O2 generation; (b) is the absorption spectrum of BPA degradation.
[0034] Figure 12 This is an evaluation of the solar energy conversion capability of the bimetallic CoZn-ZIF / ZIS heterojunction in Example 6 of the present invention.
[0035] Figure 13 5% Co in Example 7 of this invention 0.5 Zn 0.2 Cyclic test results of hydrogen peroxide production via ZIF / ZIS photocatalysis. Detailed Implementation
[0036] A method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst includes the following steps: S1 mechanical milling solid-state method for preparing bimetallic cobalt / zinc imidazole organic framework CoZn-ZIF nanoparticles, such as Figure 1 As shown: Zinc nitrate (Zn(NO3)2·6H2O) and cobalt nitrate (Co(NO3)2·6H2O) were mixed and ground, and then 2-methylimidazole was added. After mixing, the mixture was transferred to a stainless steel grinding jar equipped with steel balls (F-VC100 ball mill, Hunan Fukas Experimental Instrument Co., Ltd.) for mechanical grinding at a frequency of 20-60 Hz for 20-80 min, preferably 30-60 min. The resulting product was washed successively with deionized water and anhydrous ethanol to remove unreacted precursors, then centrifuged and vacuum dried at 60℃ for 12 hours to obtain a purple solid powder, denoted as CoZn-ZIF nanoparticles.
[0037] The molar ratio of zinc, cobalt, and 2-methylimidazole is (0.1~0.4 mmol): (0.2~0.8 mmol): (0.004~0.008 mmol).
[0038] This invention employs a simple and green mechanical grinding solid-state method to precisely prepare a series of CoZn-ZIF nanoparticles with different molar ratios by controlling the molar ratio of Co / Zn in the imidazole framework nodes.
[0039] Preparation of flower-like ZnIn2S4 materials by S2 hydrothermal method: Zinc nitrate (Zn(NO3)2·6H2O) and indium nitrate (In(NO3)3·4H2O) were dispersed in an excess solvent, and then thioacetamide (C2H5NS) was added. After magnetic stirring until completely dissolved, the resulting mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner and hydrothermally reacted at 120~180℃ for 6~14h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. The resulting product was washed several times with deionized water and anhydrous ethanol, and then vacuum dried overnight at 60℃ to obtain a flower-shaped brown ZnIn2S4 product, denoted as ZIS.
[0040] The mass ratio of zinc nitrate, indium nitrate, and thioacetamide is 0.1~0.8g: 0.3~1.2g: 0.1~0.8g; the solvent is one of ethylene glycol, N,N-dimethylformamide, and anhydrous methanol.
[0041] Preparation of CoZn-ZIF / ZIS heterojunction photocatalysts using S3: CoZn-ZIF nanoparticles and ZIS were dispersed in excess anhydrous methanol, with the amount of CoZn-ZIF nanoparticles being 2.5%–10% of the ZIS mass. After magnetic stirring at 800–1300 rpm for 2–6 h, the mixture was centrifuged and vacuum dried to constant weight to obtain the CoZn-ZIF / ZIS heterojunction photocatalyst. The mass ratio of CoZn-ZIF to ZIS is expressed as follows: x % CoZn-ZIF / ZIS.
[0042] Applications of CoZn-ZIF / ZIS heterojunction photocatalysts: This catalyst is used in the photocatalytic production of H2O2 from pure water or wastewater. This invention achieves a green and sustainable in-situ synthesis route for hydrogen peroxide through two-electron oxygen reduction. The specific process is as follows: Pure water is placed in a photocatalytic reactor without a sacrificial agent. Oxygen is introduced, and the photocatalyst CoZn-ZIF / ZIS is added in a saturated oxygen atmosphere. After dark adsorption for 30 minutes, a visible light source is turned on to carry out the photocatalytic reaction at room temperature, i.e., H2O2 is generated in situ; or Wastewater was placed in a photocatalytic reactor, with bisphenol A, an organic pollutant in the wastewater, as a sacrificial agent. Oxygen was introduced, and the photocatalyst CoZn-ZIF / ZIS was added in a saturated oxygen atmosphere. After dark adsorption for 30 min, a visible light source was turned on to carry out the photocatalytic reaction at room temperature, so as to simultaneously generate H2O2 and degrade the organic pollutant bisphenol A.
[0043] The specifications include: bisphenol A concentration in the wastewater of 5–30 mg / L; pH of the wastewater of 4–9; dosage of the photocatalyst CoZn-ZIF / ZIS of 0.20–0.50 mg / mL; and a visible light source with wavelength λ > 420 nm and light intensity ≥ 1.5 W / cm². 2 Preferably, a 300 W xenon lamp is used as the visible light source, and the distance between the reaction solution interface and the light source is 11 cm.
[0044] Example 1 A method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst includes the following steps: S1 Mechanical milling solid-state method for preparing bimetallic cobalt / zinc imidazole organic framework Co 0.2 Zn 0.1 -ZIF nanoparticles: Accurately weigh 0.030 g ZnNO3·6H2O (0.1 mmol of Zn) and 0.06 g CoNO3·6H2O (0.2 mmol of Co) into a mortar and grind until homogeneous. Then add 0.328 g 2-methylimidazole (0.004 mol) and continue grinding until homogeneous. Transfer the mixed powder to a stainless steel grinding jar equipped with a 1 cm diameter steel ball and an inner diameter of 3.5 cm, set the vibration frequency to 40 Hz, and grind for 50 min. The resulting purple product was washed successively with deionized water and anhydrous ethanol, collected by centrifugation, and dried under vacuum at 60 °C to finally obtain Co. 0.2 Zn 0.1 -ZIF nanoparticles.
[0045] Preparation of flower-like ZnIn2S4 materials by S2 hydrothermal method: Accurately weigh 0.45 g Zn(NO3)2·6H2O and 0.86 g In(NO3)3·4H2O, dissolve them in 30 mL N,N-dimethylformamide (DMF), and stir magnetically until completely dissolved; then add 0.46 g C2H5NS, and continue stirring magnetically until dissolved. Transfer the mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, and hydrothermally react at 170 ℃ for 14 h. After the reaction is complete, cool to room temperature, collect the product by centrifugation, wash successively with deionized water and anhydrous ethanol, and dry under vacuum to obtain the flower-like brown ZnIn2S4 product, denoted as ZIS.
[0046] S3 prepares 2.5% Co 0.2 Zn 0.1 -ZIF / ZIS heterojunction photocatalyst: 7.5 mg of Co 0.2 Zn 0.1 ZIF nanoparticles and 300 mg of ZIS were dispersed in 30 mL of methanol, magnetically stirred at 800–1300 rpm for 6 h, centrifuged, and vacuum dried to constant weight to obtain 2.5% Co. 0.2 Zn 0.1 -ZIF / ZIS heterojunction photocatalyst.
[0047] Example 2 A method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst includes the following steps: S1 Mechanical milling solid-state method for preparing bimetallic cobalt / zinc imidazole organic framework Co 0.2 Zn 0.1 -ZIF nanoparticles are the same as in Example 1.
[0048] The preparation of flower-shaped ZnIn2S4 material by the S2 hydrothermal method is the same as in Example 1.
[0049] S3 prepares 5% Co 0.2 Zn 0.1 -ZIF / ZIS heterojunction photocatalyst: 15 mg of Co 0.2 Zn 0.1 ZIF nanoparticles and 300 mg of ZIS were dispersed in 30 mL of methanol, magnetically stirred at 800–1300 rpm for 6 h, centrifuged, and vacuum dried to constant weight to obtain 5% Co. 0.2 Zn 0.1 -ZIF / ZIS heterojunction photocatalyst.
[0050] Example 3 A method for preparing a bimetallic MOF / zinc indium sulfide heterojunction photocatalyst includes the following steps: S1 Mechanical milling solid-state method for preparing bimetallic cobalt / zinc imidazole organic framework Co 0.5 Zn 0.2 -ZIF nanoparticles: Accurately weigh 0.060 g Zn(NO3)2·6H2O (0.2 mmol of Zn) and 0.35 g Co(NO3)2·6H2O (0.5 mmol of Co) into a mortar and grind until homogeneous. Then add 0.492 g 2-methylimidazole (0.006 mol) and continue grinding until homogeneous. Transfer the mixed powder to a stainless steel grinding jar equipped with a 1 cm diameter steel ball and an inner diameter of 3.5 cm, set the vibration frequency to 40 Hz, and grind for 50 min. The resulting purple product was washed successively with deionized water and anhydrous ethanol, collected by centrifugation, and dried under vacuum at 60 ℃ to finally obtain Co. 0.5 Zn 0.2 -ZIF nanoparticles.
[0051] The preparation of flower-shaped ZnIn2S4 material by the S2 hydrothermal method is the same as in Example 1.
[0052] S3 prepares 5% Co 0.5 Zn 0.2 -ZIF / ZIS heterojunction photocatalyst: 15 mg of Co 0.5 Zn 0.2 ZIF nanoparticles and 300 mg of ZIS were dispersed in 30 mL of methanol, magnetically stirred at 800–1300 rpm for 6 h, centrifuged, and vacuum dried to constant weight to obtain 5% Co. 0.5 Zn 0.2 -ZIF / ZIS heterojunction photocatalyst.
[0053] Comparative Example 1: Preparation of pure phase ZIF-8 by liquid phase method: 5.26 g of 2-methylimidazole was dissolved in 40 mL of methanol, and 2.18 g of Zn(NO3)2·6H2O was also dissolved in 40 mL of methanol. The 2-methylimidazole solution was then added to the Zn(NO3)2·6H2O solution, and the resulting mixture was stirred at room temperature for 4 h, followed by standing for 24 h. The white precipitate was collected by centrifugation, washed at least three times with methanol, and dried under vacuum at 60 °C for 12 h to obtain ZIF-8 (Zn-ZIF) nanoparticles.
[0054] Comparative Example 2: Preparation of pure phase ZIF-8 by mechanical grinding solid-state method: Accurately weigh 0.5 g of Zn(NO3)2·6H2O and 1.5 g of 2-methylimidazole and place them in a stainless steel grinding jar equipped with a 1 cm diameter steel ball and an inner diameter of 3.5 cm. Set the vibration frequency to 40 Hz and grind for 50 min. The resulting white precipitate was washed with deionized water and anhydrous ethanol, collected by centrifugation, and dried under vacuum at 60 °C to finally obtain ZIF-8 (Zn-ZIF) nanoparticles.
[0055] Comparative Example 3: Preparation of pure phase ZIF-67 by liquid phase method: 5.26 g of 2-methylimidazole was dissolved in 40 mL of methanol, and 4.56 g of Co(NO3)2·6H2O was also dissolved in 40 mL of methanol. The 2-methylimidazole solution was then poured into the Co(NO3)2·6H2O solution. The resulting mixture was stirred at room temperature for 4 h, and then allowed to stand for 24 h. The purple precipitate was collected by centrifugation, washed at least three times with methanol, and then vacuum dried at 60 °C for 12 h to obtain purple ZIF-67 (Co-ZIF) nanoparticles.
[0056] Comparative Example 4: Preparation of pure phase ZIF-67 by mechanical grinding solid-state method: Accurately weigh 0.5 g of Co(NO3)2·6H2O and 1.5 g of 2-methylimidazole and place them in a stainless steel grinding jar equipped with a 1 cm diameter steel ball and an inner diameter of 3.5 cm. Set the vibration frequency to 40 Hz and grind for 50 min. The resulting purple product was washed with deionized water and anhydrous ethanol, collected by centrifugation, and dried under vacuum at 60 °C to finally obtain purple ZIF-67 (Co-ZIF) nanoparticles.
[0057] Preparation of 5% Co-ZIF / ZIS (Comparative Example 5): 15 mg of Co-ZIF nanoparticles and 300 mg of ZIS were dispersed in 30 mL of methanol. After magnetic stirring at 800~1300 rpm for 6 h, the sample was centrifuged and vacuum dried to constant weight to obtain a 5% Co-ZIF / ZIS heterojunction sample.
[0058] X-ray diffraction (XRD) analysis was performed on all samples from Examples 1-3 and Comparative Examples 1-5 to characterize their crystal structures. The tested samples included: Co. 0.2 Zn 0.1 -ZIF, ZIS and 2.5% Co 0.2 Zn 0.1 -ZIF / ZIS (Example 1); Co 0.2 Zn 0.1 -ZIF and 5% Co 0.2 Zn 0.1 -ZIF (Example 2); Co 0.5 Zn 0.3 -ZIF and 5% Co 0.5 Zn 0.2-ZIF / ZIS (Example 3). Simultaneously, to verify the feasibility of preparing the metal imidazole framework by mechanical grinding, pure-phase ZIF-8 and ZIF-67 prepared by the classical liquid-phase method were compared with pure-phase ZIF-8 and ZIF-67 prepared by the mechanical grinding solid-phase method (Comparative Examples 1-4). Furthermore, to evaluate the bifunctional catalytic activity of the CoZn-ZIF / ZIS photocatalyst, a Co-ZIF / ZIS sample was prepared (Comparative Example 5). The XRD patterns of all the above samples are shown below. Figure 2 As shown. Although ZIF-8 and ZIF-67 have the same sodalite topology and similar pore size (~3.4 Å), their physicochemical properties differ significantly: the Zn-based framework endows ZIF-8 with excellent chemical / thermal stability, while the Co-based framework is rich in Co. 2+ Its coordination environment gives it an advantage in electrocatalysis. The XRD patterns of ZIF-8 (white powder) and ZIF-67 (purple powder) synthesized by the liquid phase method are shown below. Figure 2 (a) and Figure 2 As shown in (b), both exhibit the strongest diffraction peak of the (011) crystal plane at 7.3°. The pure-phase ZIF-8 and ZIF-67 prepared by mechanical grinding solid-state method also exhibit typical ZIF characteristic diffraction peaks, located at 11.06° (011), 15.18° (002), 18.07° (222), and 27.87° (242), respectively, which are basically consistent with the liquid-phase product. However, the solid-state sample shows obvious bimodal splitting at 7.38° and 7.82° (…). Figure 2 ab). This change can be attributed to mechanically induced lattice distortion: the originally equivalent {(011), (101), (110)} crystal planes produce different interplanar spacings due to anisotropic stress, causing the single peak to split into two peaks, marking the transformation of the crystal system from cubic (a=b=c) to tetragonal (a=b≠c). Furthermore, from Figure 2 (c) It can be seen that Co 0.2 Zn 0.1 -ZIF and Co 0.5 Zn 0.2 The XRD diffraction peaks of -ZIF are in perfect agreement with the characteristic peaks of pure phase ZIF-8 and ZIF-67 obtained by solid-state analysis. This result indicates that Co... 2+ With Zn 2+ The same imidazole framework can be introduced simultaneously to form bimetallic ZIF materials with tunable composition, while maintaining their crystal structure intact. Figure 2 (d) The characteristic XRD peaks of ZIS (ZnIn2S4) can be observed at 21.5°, 27.6°, and 47.2°, corresponding to the (006), (102), and (110) crystal planes on the standard card (JCPDS: 04-009-4787) of hexagonal ZnIn2S4, confirming the successful synthesis of ZnIn2S4. (Observation of Co...)0.2 Zn 0.1 -ZIF / ZIS and Co 0.5 Zn 0.2 The XRD diffraction peaks of the ZIF / ZIS samples all contain both CoZn-ZIF and ZIS diffraction peaks, and there are no impurity peaks. However, the characteristic peak of ZIS at 27.66 (102) shifts to 27.31 at a smaller angle. The reason for this is that in the heterojunction, the lattice mismatch between the two materials will generate interfacial tensile stress at the interface. Because the lattice constant of ZIS is 27.66 (102) smaller than that of CoZn-ZIF at 27.87 (242), in order to achieve "coherent growth" at the interface, the lattice of ZIS will be enlarged, causing its XRD peak to shift to a smaller angle. This tensile stress is usually caused by the strong coupling effect of interfacial chemical bonds (such as S-Zn / Co bonds). Therefore, the heterojunction is constructed by the coexistence of the CoZn-ZIF (242) crystal plane and the ZIS (102) crystal plane.
[0059] ZnIn2S4 (ZIS) obtained in Example 2 and 5% Co 0.2 Zn 0.1 -ZIF / ZIS sample, 5% Co obtained in Example 3 0.5 Zn 0.2 FTIR spectrometry was performed on ZIF / ZIS samples, ZIF-67 samples prepared by liquid-phase method and solid-phase method obtained from Comparative Examples 3-5, and Co-ZIF / ZIS samples, respectively. The results are as follows: Figure 3 As shown. By Figure 3 (a) It is evident that the chemical composition and surface functional groups of ZIF-67 obtained by both the liquid-phase and solid-phase methods are not significantly different, indicating that the two synthetic routes have equivalent effects on the chemical structure of the product. 1563cm -1 up to 563cm -1 The characteristic peaks in the wavelength range are attributed to the bending vibrations of the imidazole ring. ZIF-8 and ZIF-67 samples prepared by liquid-phase and solid-phase methods, respectively, show peaks at 421 cm⁻¹. -1 The presence of Co-N and Zn-N bending vibration absorption peaks at all locations, with identical peak positions, confirms that the bimetallic ions have similar coordination microenvironments within the framework. The FTIR absorption peaks of characteristic functional groups in bimetallic CoZn-ZIF with different Co / Zn molar ratios are completely consistent with the characteristic peaks of functional groups in pure-phase ZIF-67. Combined with XRD pattern analysis, this demonstrates the successful synthesis of bimetallic CoZn-ZIF.
[0060] contrast Figure 3 (b) ZIS, 5% Co 0.2 Zn 0.1 -ZIF / ZIS, 5%Co 0.5 Zn 0.2The FTIR spectra of ZIF / ZIS and Co-ZIF / ZIS samples show that pure ZIS at 753 cm⁻¹... -1 There is no characteristic absorption nearby, but a weak absorption peak is observed at this location for Co-ZIF / ZIS and CoZn-ZIF / ZIS heterojunction samples. This peak can be attributed to the bending vibration of the Co-S bond at the heterojunction interface, indicating that the Co atoms on the imidazole framework have formed chemical bonds with the S atoms on the ZIS surface. This provides direct spectroscopic evidence for the close contact at the heterojunction interface.
[0061] X-ray photoelectron spectroscopy (XPS) was used to study Co 0.5 Zn 0.2 -ZIF, 5% Co 0.5 Zn 0.2 Surface chemical composition and elemental valence state analysis were performed on ZIF / ZIS and Co-ZIF samples, and the results are as follows: Figure 4 As shown. Figure 4 XPS full spectrum (a) shows the detection of C, N, O, Co, In, Zn, and S elements in the CoZn-ZIF / ZIS composite material, confirming the presence of all components in the composite system. High-resolution XPS spectra further reveal the chemical states of each element. Figure 4 As shown in (b), the Co 2p spectrum of pure ZIF-67 exhibits two characteristic peaks at 783.3 eV and 799.2 eV, which are attributed to Co 2p, respectively. 3 / 2 and Co 2p 1 / 2 In the bimetallic CoZn-ZIF, these two peaks shift negatively to 782.29 eV and 797.20 eV, respectively; while in the CoZn-ZIF / ZIS composite, they shift further negatively to 779.2 eV and 795.0 eV, indicating that Co... 2+ The electron density continues to increase, and the coordination environment undergoes significant changes. For example... Figure 4 As shown in (c), Zn 2p in CoZn-ZIF 3 / 2 and Zn 2p 1 / 2 The binding energies of Zn and Zn are 1023.58 eV and 1046.73 eV, respectively. In the CoZn-ZIF / ZIS composite material, they decrease slightly to 1023.28 eV and 1046.30 eV, respectively. The change is small, indicating that the electronic structure of Zn is relatively weakly affected by the heterostructure. Figure 4 As shown in (d), S 2p in pure ZIS 3 / 2 and S 2p 1 / 2 The characteristic peaks are located at 160.69 eV and 161.81 eV; in the CoZn-ZIF / ZIS composite material, these two peaks increase to 161.74 eV and 163.9 eV, respectively, while a new peak appears at 170.96 eV for edge S atoms. Figure 4 (e) shows that in pure ZIS, In 3d 5 / 2 and In3d 3 / 2 The binding energies of the original ZIS and CoZn-ZIF composites were 444.20 eV and 451.74 eV, respectively, and both increased to 445.14 eV and 454.46 eV after composite formation. The XPS shift trends observed above show that compared to pure ZIS and pure CoZn-ZIF composites, the binding energies of S 2p and In 3d are significantly increased, while the binding energies of Co 2p and Zn 2p are significantly decreased. This opposite shift direction indicates that at the heterojunction interface, the electron density decreases (electron loss) on the ZIS side and increases (electron gain) on the CoZn-ZIF side, meaning that photogenerated electrons spontaneously transfer from ZIS to CoZn-ZIF. This electron transfer process establishes a built-in electric field (IEF) at the interface, pointing from ZIS to CoZn-ZIF. Under visible light irradiation, ZIS and CoZn-ZIF are simultaneously excited to generate electron-hole pairs. The built-in electric field further guides the directional migration of charge carriers, forming a stable Z-scheme heterostructure. This Z-scheme mechanism not only effectively promotes the spatial separation of photogenerated electrons and holes, but also retains the strongest redox capabilities of each component, thereby significantly enhancing the efficiency of photocatalytic reactions.
[0062] ZnIn2S4 and Co obtained in Example 3 0.5 Zn 0.2 -ZIF, 5%Co 0.5 Zn 0.2 The ZIF / ZnIn2S4 sample and the Co-ZIF sample obtained in Comparative Example 4 were subjected to SEM tests, and the results are as follows: Figure 5 As shown.
[0063] The morphological characteristics of ZIF-67 prepared by mechanical grinding solid-phase method are significantly different from those of products prepared by traditional liquid-phase method. Figure 5 The SEM image in (a) clearly shows that ZIF-67 synthesized by the liquid-phase method consists of regularly morphologically regular rhombic dodecahedral nanocrystals. In contrast, ZIF-67 obtained by the solid-phase method ( Figure 5 b) The crystals are regular tetragonal prismatic crystals with smooth surfaces and good dispersion. This morphological difference is consistent with the XRD results: mechanically induced lattice distortion causes anisotropic strain in the originally equivalent {(011), (101), (110)} crystal planes, and the interplanar spacing is no longer equal. Tension occurs only along specific crystal plane directions, causing the original single peak at 7.3° to split into a double peak at 7.38° and 7.82°, marking a transformation of the crystal system from cubic (a=b=c) to tetragonal (a=b≠c). For example... Figure 5As shown in (c), the bimetallic CoZn-ZIF exhibits neatly arranged and uniformly sized short rod-shaped crystals, which show a significant axial shortening compared to the monometallic Co-ZIF. This indicates that Co and Zn have jointly entered the imidazole framework, confirming the formation of the bimetallic CoZn-ZIF imidazole organic framework. Figure 5 As shown in (d), the ZIS (ZnIn2S4) product exhibits flower-like microparticles assembled from nanosheets. Figure 5 (e) shows 5% Co 0.5 Zn 0.2 SEM image of the -ZIF / ZIS composite. Due to the strong built-in electric field formed by the strong bonding at the Co–S interface, a tight interfacial coupling occurs between the 2D sheet-like ZIS and the 3D short rod-shaped CoZn-ZIF, making it difficult to clearly distinguish the SEM morphology of the CoZn-ZIF monomer crystal. To further demonstrate the 5% Co... 0.5 Zn 0.2 The successful synthesis of the ZIF / ZIS complex was achieved by bombarding the sample with a high-energy electron beam using SEM, which excited the characteristic X-rays unique to the elements contained in the sample. Figure 5 (f) The EDS detector analyzed the energy of these X-rays to determine the presence of In, S, Zn, C, N, and Co elements in the sample (qualitative analysis) and their relative abundance (semi-quantitative analysis), which was consistent with XPS results. Furthermore, In, S, Zn, and Co elements were uniformly attached to the flower-like ZIS surface and well dispersed.
[0064] The band structure and band gap of semiconductor materials have a significant impact on photocatalytic activity. To investigate the reasons for the improved catalytic performance, the UV-Vis diffuse reflectance spectra of ZIF-8, ZIF-67, ZIS, and CoZn-ZIF / ZIS samples obtained in Examples 1-3 and Comparative Examples 2 and 4 were measured to study their light collection capabilities. The results are as follows: Figure 6 As shown, the pure-phase ZIF-8 prepared by the solid-state method only responds to ultraviolet light at approximately 250 nm, while the pure-phase ZIF-67 and ZIS both respond to visible light. The UV-Vis spectrum of ZIF-67 shows two absorption characteristics: an absorption peak near 380 nm related to the π→π* transition in the imidazole ring, and a sideband absorption peak at 655 nm, which can be attributed to the Co ion in the tetrahedral crystal field. 4 A2(F) → 4 The transition induced by the T1(P) energy level indicates that ZIF-67 nanosheets possess preferential light-collecting ability in the visible light region, while the absorption sideband of pure-phase ZIS is at 625 nm. Compared to pure-phase ZIS (625 nm) and ZIF-67 (655 nm), the heterojunction composite material exhibits enhanced light absorption. (5% Co) 0.5 Zn 0.2-ZIF / ZIS extends the optical absorption edge to 780 nm, which is superior to 2.5% Co. 0.2 Zn 0.1 -ZIF / ZIS (675 nm) 2.5% Co 0.2 Zn 0.1 -ZIF / ZIS (630 nm), this improvement is mainly attributed to Co 0.5 Zn 0.2 The tight bonding at the interface between ZIF and ZIS alters the electronic structure of the photocatalyst surface, providing more active sites and promoting efficient charge carrier transport. This further supports the beneficial role of CZn-ZIF in enhancing the photocatalytic performance of ZIS semiconductor catalysts.
[0065] Fluorescence is another important method for measuring the recombination rate of photogenerated carriers. This means that at the same energy level, excited electrons transition back to the ground state, thus concentrating energy and releasing it as fluorescence at a specific wavelength. The weaker the fluorescence peak intensity, the lower the recombination efficiency of photogenerated electrons, and the better the catalyst performance. Therefore, fluorescence tests were performed on the ZIS samples obtained in Examples 1-3, the CoZn-ZIF / ZIS sample, and the Co-ZIF / ZIS sample obtained in Comparative Example 5. The results are as follows: Figure 7 As shown. ZIS, Co-ZIF / ZIS, and 2.5% Co 0.2 Zn 0.1 -ZIF / ZIS, 5%Co 0.2 Zn 0.1 -ZIF / ZIS and 5%Co 0.5 Zn 0.2 The fluorescence spectra of the -ZIF / ZIS samples showed similar characteristic emission peaks around 664 nm at an excitation wavelength of 330 nm. Compared to pure-phase ZIS, the fluorescence intensity of the bimetallic CoZn-ZIF / ZIS after excitation was significantly reduced, indicating that the introduction of CoZn-ZIF effectively suppressed charge recombination of ZIS. Among them, 5% Co... 0.5 Zn 0.2 The -ZIF / ZIS sample exhibits the lowest fluorescence intensity, and its photogenerated charge separation efficiency is far higher than that of pure ZIS.
[0066] The photocatalytic performance of semiconductor photocatalysts is largely influenced by the trapping and lifetime of photoinduced charge carriers. To explore the influence of photogenerated charge behavior in CoZn-ZIF / ZIS, the ZIS and 5% Co obtained in Examples 2-3 were compared. 0.2 Zn 0.1 -ZIF / ZIS and 5%Co 0.5 Zn 0.2Photoelectrochemical measurements were performed on the ZIF / ZIS sample and the ZIF-67 / ZIS sample obtained in Comparative Example 5. Transient photocurrent response and electrochemical impedance spectroscopy (EIS) were measured using an electrochemical workstation under a 300W xenon lamp. A three-electrode system was formed using a Pt sheet as the counter electrode, Ag / AgCl as the reference electrode, and FTO conductive glass coated with the material as the working electrode. Figure 8 As shown in (a), pure ZIS, ZIF-67 / ZIS and 5% Co 0.2 Zn 0.1 -ZIF / ZIS and 5%Co 0.5 Zn 0.2 Transient photocurrent response of ZIF / ZIS samples during multiple switching cycles under visible light exposure, 5% Co 0.5 Zn 0.2 The ZIF / ZIS composite exhibited the highest photocurrent intensity, exceeding that of ZIS and ZIF-67 / ZIS. These results indicate that the separation and transfer capabilities of photoexcited carriers are enhanced in the composite material. Furthermore, Figure 8 (b) shows the electrochemical impedance spectroscopy (EIS) curves for pure ZIS, ZIF-67 / ZIS, and heterojunction 5% Co. 0.2 Zn 0.1 -ZIF / ZIS and 5%Co 0.5 Zn 0.2 The comparison of ZIF / ZIS samples further confirmed this finding, because 5% Co 0.5 Zn 0.2 -ZIF / ZIS exhibits the smallest Nyquist radius.
[0067] Applications of bimetallic MOF-zinc sulfide indium heterojunction photocatalytic hydrogen peroxide production Example 4: In a pure water system, the CoZn-ZIF / ZIS photocatalytic system exhibits both selectivity and high efficiency in H2O2 generation.
[0068] Select ZIS and 2.5% Co obtained from Examples 1-3 0.2 Zn 0.1 -ZIF / ZIS, 5%Co 0.2 Zn 0.1 -ZIF / ZIS, and 5%Co 0.5 Zn 0.2 The -ZIF / ZIS sample and the 5%Co-ZIF / ZIS obtained in Comparative Example 5 were used as photocatalysts to produce H2O2 in pure water.
[0069] 50 mL of pure water was placed in a quartz reactor equipped with a water bath circulation system. Oxygen was introduced for 30 min, and then 15 mg of photocatalyst was added. The reactor was sealed with aluminum foil and stirred in the dark for 30 min to reach adsorption-desorption equilibrium. A xenon lamp (300 W) with a visible light source (λ>420 nm) was turned on, and the photocatalytic reaction was carried out under visible light irradiation. A sample (1 mL) was taken every 30 min, filtered through a 0.22 μm nylon aqueous filter membrane, and the cumulative amount of H2O2 produced in situ by photometry was determined.
[0070] Determination of H2O2 content: Add 1 mL of 0.1 M potassium hydrogen phthalate solution and 1 mL of 0.4 M potassium iodide solution to 1 mL of the sample solution to obtain a mixed solution. Shake the mixture and place it in the dark for 1 h. Then measure its absorbance at 350 nm. Finally, determine the H2O2 content according to the H2O2 standard curve (see [reference]). Figure 10 ) C H2O2 =( A-0.0268) / 2.5554 to calculate the amount of H2O2 produced by the photocatalyst at different time periods.
[0071] Photocatalysis experiments were conducted under visible light using pure water as the reaction solvent. Figure 9 (a) The absorption spectra of H2O2 produced by ZIS samples under different illumination times; Figure 9 (b) Under the same conditions, 5% Co 0.5 Zn 0.2 The corresponding spectra of -ZIF / ZIS samples. Figure 9 (c) Comparisons were made between pure-phase ZnIn2S4 (ZIS) (Examples 1-3), a 5% ZIF-67 / ZIS heterojunction with a single-metal imidazole framework (Comparative Example 5), and a 2.5% Co bimetallic imidazole framework. 0.2 Zn 0.1 -ZIF / ZIS, 5%Co 0.2 Zn 0.1 -ZIF / ZIS, 5%Co 0.5 Zn 0.2 -ZIF / ZIS heterojunctions (Examples 1-3) achieved a photocatalytic H2O2 production rate of 453 µmol·g under visible light. -1 ·h -1 791µmol·g -1 ·h -1 854µmol·g -1 ·h -1 1528µmol·g -1 ·h -1 and 2277 µmol·g -1 ·h -1 .from Figure 9(d) 5% Co can be observed 0.5 Zn 0.2 -ZIF / ZIS heterojunction photocatalytic H2O2 production rate (2277 µmol·g) -1 ·h -1 The rate of H2O2 production by pure-phase ZIS photocatalysis (453 µmol·g) is... -1 ·h -1 It is about 5 times that of ZIF-67 / ZIS (791 µmol·g) -1 ·h -1 The efficiency is approximately 2.8 times higher. This indicates that the bimetallic CoZn-ZIF enhances the oxygen absorption of ZnIn2S4 while lowering the energy barrier of its two-electron oxygen reduction reaction, providing a new approach for constructing heterojunction materials that can efficiently generate H2O2 under sunlight irradiation.
[0072] Example 5: In BPA wastewater, the CoZn-ZIF / ZIS photocatalytic system achieved a simultaneous increase in H2O2 yield and BPA degradation efficiency.
[0073] A concentration of 20 mg·L -1 50 mL of BPA solution was placed in a quartz reactor equipped with a water bath circulation system, oxygen was introduced for 30 min, and 15 mg of the photocatalyst 5% Co obtained in Example 3 was added in a saturated oxygen atmosphere. 0.5 Zn 0.2 -ZIF / ZIS. Seal with aluminum foil and stir in the dark for 30 minutes to reach adsorption-desorption equilibrium. Turn on a xenon lamp (300 W) with a visible light source (λ>420 nm) to carry out the photocatalytic reaction under visible light irradiation. Take samples (1 mL each time) every 30 minutes, filter through a 0.22 μm nylon aqueous filter membrane, and measure the photocatalytic in-situ H2O2 production and simultaneous BPA degradation effects by photometry.
[0074] Determination of H2O2 content: Add 1 mL of 0.1 M potassium hydrogen phthalate solution and 1 mL of 0.4 M potassium iodide solution to 1 mL of the sample solution to obtain a mixed solution. Shake the mixture and place it in the dark for 1 h. Then measure its absorbance at 350 nm. Finally, determine the H2O2 content according to the H2O2 standard curve (see [reference]). Figure 10 ) C H2O2 The amount of H2O2 produced by the photocatalyst at different time periods was calculated using (A-0.0268) / 2.5554, and the results are as follows: Figure 11 As shown in (a).
[0075] Determination of BPA degradation rate: Take 1 mL of sample solution, dilute with purified water to 3 mL, shake the mixture, and place it in a quartz cuvette for spectral scanning (230~500 nm). The maximum absorption peak is 275 nm. Finally, the BPA degradation efficiency % is calculated as follows: % = ((A0-A...) t ) / A0)×100%, where: A0 is the initial absorbance of BPA, A t (The absorbance of BPA corresponds to the light irradiation time). Then, the degradation efficiency of BPA for different light irradiation times was calculated, and the results are as follows: Figure 11 As shown in (b).
[0076] Example 6 This invention also evaluated the solar energy conversion capability of the bimetallic CoZn-ZIF / ZIS heterojunction. For example... Figure 12 As shown, the H2O2 generation rate of this system is as high as 2236.5 µmol·g. -1 ·h -1 And for BPA (20 mg·L⁻¹) -1 The degradation efficiency reached 60.5%. Further mechanistic studies showed that BPA and other recalcitrant organic compounds can act as hole sacrificial agents, significantly improving the separation efficiency of photogenerated electron-hole pairs. The enriched electrons then participate in the two-electron oxygen reduction process, continuously generating H2O2, thereby achieving a synergistic effect of pollutant degradation and H2O2 resource generation.
[0077] Example 7: Purification, recovery, and reuse of CoZn-ZIF / ZIS photocatalyst.
[0078] To evaluate the purification and recovery performance and reuse potential of the photocatalyst, 5% Co from Example 4 was selected. 0.5 Zn 0.2 -ZIF / ZIS materials were subjected to H2O2 generation experiments under pure water conditions (without added sacrificial agents) to evaluate their cycle stability.
[0079] (1) First experiment: 50 mL of pure water was placed in a quartz reactor equipped with a water bath circulation system, oxygen was introduced for 30 min, and 15 mg of the photocatalyst 5% Co obtained in Example 3 was added in a saturated oxygen atmosphere. 0.5 Zn 0.2 -ZIF / ZIS, sealed with tin foil, stirred in the dark for 30 minutes to reach adsorption-desorption equilibrium. A xenon lamp (300 W) with a visible light source (λ>420 nm) was turned on, and the photocatalytic reaction was carried out under visible light irradiation. A sample (1 mL) was taken every 30 minutes, filtered through a 0.22 μm nylon aqueous filter membrane, and the cumulative amount of H2O2 produced in situ by photometry was determined.
[0080] Determination of H2O2 content: Add 1 mL of 0.1 M potassium hydrogen phthalate solution and 1 mL of 0.4 M potassium iodide solution to 1 mL of the sample solution to obtain a mixed solution. Shake the mixture and place it in the dark for 1 h. Then measure its absorbance at 350 nm. Finally, determine the H2O2 content according to the H2O2 standard curve (see [reference]). Figure 10 ) C H2O2 =( A-0.0268) / 2.5554 to calculate the amount of H2O2 produced by the photocatalyst at different time periods.
[0081] (2) Second experiment: To investigate the regeneration performance of the catalyst, the solid-liquid mixture after the first photocatalytic reaction was centrifuged and the solid was collected. The solid was transferred to the photocatalytic reactor, and an acidic ethanol solution with pH=3~4 (ethanol:water=60:40, volume ratio (mL / mL)) was added. The reactor was then irradiated with visible light. The photocatalytic regeneration process was repeated twice in the above manner, with centrifugation after each process. Finally, the obtained product was vacuum dried to complete the recovery.
[0082] The resulting purified and recovered 5% Co 0.5 Zn 0.2 The ZIF / ZIS photocatalyst was tested again after the first experiment, and its performance in producing hydrogen peroxide was tested. The remaining solid-liquid mixture in the centrifuge tube was retained for later use.
[0083] (3) Third experiment: The solid-liquid mixture remaining from the second photocatalysis experiment was centrifuged, washed, and vacuum dried. The collected residual solid from the second photocatalysis experiment was purified and recovered again. The solid was transferred to the photocatalytic reactor, and an acidic ethanol solution with pH=3~4 (ethanol:water=60:40, volume ratio (mL / mL)) was added. The reactor was then irradiated under visible light. The "photocatalytic regeneration" process was repeated twice in the above manner. After each process, the solid was centrifuged, and the resulting product was finally vacuum dried to complete the recovery.
[0084] The 5% Co obtained after further purification and recovery 0.5 Zn 0.2 The ZIF / ZIS photocatalyst was tested a second time to assess its hydrogen peroxide production performance. The remaining solid-liquid mixture in the centrifuge tube was retained for later use.
[0085] Cyclic stability test (see) Figure 13 This indicates that 5% Co 0.5 Zn 0.2 -ZIF / ZIS reacted after three consecutive light irradiations, resulting in an H2O2 concentration of 2236 µmol·g. -1 ·h -1 Slightly decreased to 1752 µmol·g -1 ·h -1Analysis suggests that the slight degradation is primarily due to mass loss during centrifugal recovery, rather than degradation of the catalyst's bulk structure or surface active sites. This is attributed to the robust interfacial contact between CoZn-ZIF and ZIS, effectively ensuring the structural integrity of the heterojunction after multiple cycles. Further experiments using the recovered catalyst for H2O2-synergistic BPA degradation showed that the BPA degradation rate slightly decreased from 60.5% to 54.8% after three cycles. Purification, recovery, and reuse experiments demonstrated no significant degradation in the oxygen reduction activity of photogenerated electrons or the oxidative degradation efficiency of photogenerated holes, fully confirming the excellent stability and regeneration potential of the CoZn-ZIF / ZIS photocatalyst in a bifunctional synergistic system.
[0086] In summary, this invention synthesizes CoZn-ZIF using a solid-state method and employs an interface engineering control strategy to directionally match the CoZn-ZIF (242) crystal plane with the flower-like ZnIn2S4 (102) crystal plane, optimizing the interfacial contact structure and constructing a tightly bonded Z-type CoZn-ZIF / ZnIn2S4 heterojunction composite. This material exhibits an extended light absorption edge to 780 nm, demonstrating excellent visible light capture capability; its internal ordered interface can establish carrier transport pathways, achieving efficient electron-hole spatial separation. Under visible light irradiation, in an air atmosphere, and without any sacrificial agents, the photocatalyst achieves a H2O2 yield of 2277 µmol·g in a pure water system. -1 ·h -1 When used with bisphenol A (BPA, 20 mg·L⁻¹) -1 In the actual wastewater system, the H2O2 yield was further increased to 2236.5 µmol·g. -1 ·h -1 Meanwhile, the degradation efficiency of BPA is 60.5%. Compared with the highly polluting and energy-intensive anthraquinone process and the equipment-dependent electrocatalytic process, this invention can drive the reaction using only visible light, water, and air. It is low-cost, green, and pollution-free, providing a sustainable new technical solution for the fields of green chemistry and clean energy.
Claims
1. A method for preparing a bimetallic MOF / indium zinc sulfide heterojunction photocatalyst, comprising the following steps: Preparation of bimetallic cobalt / zinc imidazole organic framework CoZn-ZIF nanoparticles by S1 mechanical milling solid-state method: Zinc nitrate and cobalt nitrate were mixed and ground, and then 2-methylimidazole was added. After mixing, the mixture was transferred to a stainless steel grinding jar equipped with steel balls for mechanical grinding. The resulting product was washed, centrifuged, and vacuum dried to obtain a purple solid powder, which was denoted as CoZn-ZIF nanoparticles. Preparation of flower-like ZnIn2S4 materials by S2 hydrothermal method: Zinc nitrate and indium nitrate were dispersed in an excess solvent, and then thioacetamide was added. After magnetic stirring until completely dissolved, the resulting mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner for hydrothermal reaction. After the reaction was completed, the solution was cooled to room temperature, centrifuged, washed, and vacuum dried to obtain a flower-shaped brown ZnIn2S4 product, denoted as ZIS. Preparation of CoZn-ZIF / ZIS heterojunction photocatalysts using S3: CoZn-ZIF nanoparticles and ZIS were dispersed in excess anhydrous methanol, and after magnetic stirring, centrifugation and vacuum drying were performed to obtain the CoZn-ZIF / ZIS heterojunction photocatalyst.
2. The preparation method of the bimetallic MOF / indium zinc sulfide heterojunction photocatalyst as described in claim 1, characterized in that: In step S1, the molar ratio of zinc, cobalt, and 2-methylimidazole is (0.1~0.4 mmol):(0.2~0.8 mmol):(0.004~0.008 mmol).
3. The preparation method of the bimetallic MOF / zinc indium sulfide heterojunction photocatalyst as described in claim 1, characterized in that: The mechanical grinding conditions in step S1 refer to a frequency of 20~60Hz and a time of 20~80min.
4. The preparation method of the bimetallic MOF / zinc indium sulfide heterojunction photocatalyst as described in claim 1, characterized in that: In step S2, the mass ratio of zinc nitrate, indium nitrate, and thioacetamide is 0.1~0.8g: 0.3~1.2g: 0.1~0.8g; the solvent is one of ethylene glycol, N,N-dimethylformamide, and anhydrous methanol.
5. The preparation method of the bimetallic MOF / zinc indium sulfide heterojunction photocatalyst as described in claim 1, characterized in that: The hydrothermal reaction conditions in step S2 refer to a temperature of 120~180℃ and a time of 6~14h.
6. The method for preparing a bimetallic MOF / indium zinc sulfide heterojunction photocatalyst as described in claim 1, characterized in that: In step S3, the amount of CoZn-ZIF nanoparticles used is 2.5% to 10% of the ZIS mass.
7. A CoZn-ZIF / ZIS heterojunction photocatalyst prepared by the method according to any one of claims 1 to 6.
8. The application of the CoZn-ZIF / ZIS heterojunction photocatalyst as described in claim 7, characterized in that: This catalyst is used in the photocatalytic production of H2O2 from pure water or wastewater.
9. The application of the CoZn-ZIF / ZIS heterojunction photocatalyst as described in claim 8, characterized in that: The photocatalytic H2O2 production process is as follows: Pure water is placed in a photocatalytic reactor without a sacrificial agent. Oxygen is introduced, and the photocatalyst CoZn-ZIF / ZIS is added in a saturated oxygen atmosphere. After dark adsorption for 30 minutes, a visible light source is turned on to carry out the photocatalytic reaction at room temperature, i.e., H2O2 is generated in situ; or Wastewater was placed in a photocatalytic reactor, with bisphenol A, an organic pollutant in the wastewater, as a sacrificial agent. Oxygen was introduced, and the photocatalyst CoZn-ZIF / ZIS was added in a saturated oxygen atmosphere. After dark adsorption for 30 min, a visible light source was turned on to carry out the photocatalytic reaction at room temperature, so as to simultaneously generate H2O2 and degrade the organic pollutant bisphenol A.
10. The application of the CoZn-ZIF / ZIS heterojunction photocatalyst as described in claim 9, characterized in that: The concentration of bisphenol A in the wastewater is 5-30 mg / L; the pH of the wastewater is 4-9; the dosage of the photocatalyst CoZn-ZIF / ZIS is 0.20-0.50 mg / mL; the wavelength of the visible light source is >420 nm, and the light intensity is ≥1.5 W / cm². 2 .